(untitled) - Kumru Şenyaşar Meterelliyoz; Menekşe Sıla Yazar (Psikiyatride Güncel Yaklaşımlar, 2020)
Albinism is an inherited condition that may cause mental challenges in individuals. The aim of this study was to investigate the psychiatric distress that individuals with albinism experienced, the level of emotional impact caused by albinism on the quality of life and self-esteem. Twenty individuals with albinism, 20 individuals with vitiligo, 20 healthy controls included to the study. Participants were administered Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Coopersmith’s Self-Esteem Inventory (CSEI), World Health Organization Questionnaire on Quality of Life: Short Form (WHOQOL-BREF). BDI, BAI scores of individuals with albinism were significantly higher. The physical health, psychological, social relationship domain scores of the individuals with albinism were significantly lower than in healthy controls. Individuals with albinism had lower scores on Environment domain scores were lower than both those with vitiligo and healthy controls. The physical health, psychological, social relationship domain scores were negatively correlated with BDI; the physical health and environment domain scores were negatively correlated with BAI scores in albinism group. The CSEI scores of individuals with albinism were significantly lower than in healthy controls. According to our findings, the higher levels of depression and anxiety, lower levels of self-esteem, and quality of life indicate psychosocial distress among the individuals with albinism. Determination of the psychosocial distress experienced by individuals with albinism will contribute in better understanding of the experience of individuals with albinism and public awareness on albinism.